Using script theory to cultivate illness script formation and clinical reasoning in health professions education - Lubarsky, Stuart; Dory, Valérie; Audétat, Marie-Claude; Custers, Eugène; Charlin, Bernard (Canadian Medical Education Journal, 2015)
Background: Script theory proposes an explanation for how information is stored in and retrieved from the human mind to influence individuals’ interpretation of events in the world. Applied to medicine, script theory focuses on knowledge organization as the foundation of clinical reasoning during patient encounters. According to script theory, medical knowledge is bundled into networks called ‘illness scripts’ that allow physicians to integrate new incoming information with existing knowledge, recognize patterns and irregularities in symptom complexes, identify similarities and differences between disease states, and make predictions about how diseases are likely to unfold. These knowledge networks become updated and refined through experience and learning. The implications of script theory on medical education are profound. Since clinician-teachers cannot simply transfer their customized collections of illness scripts into the minds of learners, they must create opportunities to help learners develop and fine-tune their own sets of scripts. In this essay, we provide a basic sketch of script theory, outline the role that illness scripts play in guiding reasoning during clinical encounters, and propose strategies for aligning teaching practices in the classroom and the clinical setting with the basic principles of script theory.